An Effect of Wind Veer on Wind Turbine Performance - Undarmaa Tumenbayar; Kyungnam Ko (International Journal of Renewable Energy Development, 2023)
An investigation was performed to identify the wind veer impact on wind turbine power performance at a wind farm located on Jeju Island, South Korea. A 2 MW wind turbine was used as a test turbine. An 80 m-tall met mast was located 220 m away from the test wind turbine and a ground lidar was installed close to the met mast. The wind veer conditions were divided into four types: veering in upper and lower rotor (VV), veering in upper and backing in lower rotor (VB), backing in upper and lower rotor (BB) and backing in upper and veering in lower rotor (BV). The frequency of the four types was identified at the wind farm. The characteristics of wind veer was analysed in terms of diurnal variation and wind speed. In addition, the power curves of the four types were compared with that under no veer condition. Also, the power deviation coefficient (PDC) derived from the power outputs was calculated to identify the effect of the four types on the turbine power performance. As a result, the frequencies of the types, VV, VB, BB and BV were 62.7 %, 4.9 %, 9.2 % and 23.1 %, respectively. The PDCs for the types VV and BV were 3.0 % and 4.2 %, respectively, meaning a power gain while those for the types VB and BB were -2.9 % and -3.9 %, respectively, meaning a power loss.